问题 解答题
[1-(
1
4
+
3
8
)]÷
1
4
1
3
-
1
5
)×45
19
13
÷
7
5
-
6
13
×
5
7
8
13
÷7+
1
7
×
6
13
7
9
×9+
7
9
2-
6
13
÷
9
26
-
2
3
答案

(1)[1-(

1
4
+
3
8
)]÷
1
4

=[1-

5
8
]×4,

=

3
8
×4,

=1

1
2

(2)(

1
3
-
1
5
)×45,

=

1
3
×45-
1
5
×45,

=15-9,

=6;

(3)

19
13
÷
7
5
-
6
13
×
5
7

=

19
13
×
5
7
-
6
13
×
5
7

=(

19
13
-
6
13
)×
5
7

=1×

5
7

=

5
7

(4)

8
13
÷7+
1
7
×
6
13

=

8
13
×
1
7
+
1
7
×
6
13

=(

8
13
+
6
13
)×
1
7

=

14
13
×
1
7

=

2
13

(5)

7
9
×9+
7
9

=7+

7
9

=7

7
9

(6)2-

6
13
÷
9
26
-
2
3

=2-

6
13
×
26
9
-
2
3

=2-(

4
3
+
2
3
),

=2-2,

=0.

单项选择题
单项选择题 A1/A2型题